THE INFLUENCING FACTORS AFFECTING CONSUMER’S INTENTION TO CONTINUOUS USE OF E-WALLET: A PROPOSED MODEL - Mohamad Fakhrul Reza Abd Rahman; Shaizatulaqma Kamalul Ariffin, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The purpose of this study is to review the relationship between perceived ease of use, perceived usefulness, attitude, subjective norm, perceived behavioural control, disconfirmation and user satisfaction and consumers’ intention to continuous use. In specific, this study intends to propose a model to identify the influencing factors on this behaviour. This study also proposed a moderator variable which is perceived value. The hypothesis on the proposed framework of this study will be tested, taking the sample of consumers, to determine the factors that affect the continuous to use of e-wallet in Malaysia. The discoveries will be useful as reference for further studies on analysing or evaluating the use of e-wallet payment, to support the rapidly growing cashless society in Malaysia.